2015
DOI: 10.1212/wnl.0000000000001968
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up evaluation of oculomotor performance with fMRI in the subacute phase of concussion

Abstract: Objective: To expand on our previous study by performing a follow-up testing session in the subacute phase of injury for participants recently diagnosed with a concussion.Methods: A battery of oculomotor tests were administered to participants 30 days postconcussion while simultaneous fMRI was performed.Results: Three of the 7 oculomotor tasks (antisaccade, self-paced saccade, and memory-guided saccade) administered showed significant differences between the recently concussed group compared with normal volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
71
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 11 publications
8
71
1
Order By: Relevance
“…These results indicate that individuals may not recognise the persistence of symptoms post-mTBI. Collectively the findings from the symptomatic and asymptomatic mTBI groups align with previous research reporting persistent physiological and sensorimotor impairment following mTBI (8,11,13,14).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results indicate that individuals may not recognise the persistence of symptoms post-mTBI. Collectively the findings from the symptomatic and asymptomatic mTBI groups align with previous research reporting persistent physiological and sensorimotor impairment following mTBI (8,11,13,14).…”
Section: Discussionsupporting
confidence: 86%
“…Studies have demonstrated persistent multi-system impairments, particularly sensorimotor and physiological disturbances, following mTBI, beyond expected recovery times (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and following self-reported symptom abatement (8,11,13,14). One recent review (18) identified persistent impairments in 36 individual sensorimotor and/or physiological variables (postural control, oculomotor function, and sleep) in individuals subacutely post mTBI, with additional meta-analysis evidence of impaired heart-beat regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The sequelae of concussion, a mild TBI, might be underestimated [19,20]. The World Health Organization Collaborating Center for Neurotrauma Task Force has estimated that up to 70%–90% of all traumatic brain injuries are treated as a mild TBI or concussion [21].…”
Section: Discussionmentioning
confidence: 99%
“…The antisaccade may be a better indicator of impaired brain function in concussion than previous tests have been (Balaban et al, 2016;Heitger et al, 2004;Heitger et al, 2006;Hoffer et al, 2017). For example, persons in the acute and subacute stages of concussion elicited a marked and persistent deficit in antisaccade RTs as compared to age-matched healthy controls, whereas no such persistent deficit was identified via prosaccades (Johnson, Hallett, & Slobounov, 2015a;Johnson, Zhang, Hallett, & Slobounov, 2015b). It therefore may be the case that the executive demands associated with antisaccades provide adequate resolution to detect subtle deficits arising from a concussion and may provide a valid tool for identifying recovery of function and determining a timeline for safe return to play (Webb et al, 2018).…”
Section: Discussionmentioning
confidence: 95%